Perceção internacional de Portugal como destino turístico - Sousa, Vânia (2021)
The tourism market is under continuous development; hence, there is a strong demand for tourist destinations to maximise their competitive advantages. This article aims to identify the international perception of Portugal as a tourism destination, and identify which aspects are more valued according to international tourists, thereby increasing competitiveness. A survey was given to foreigners who had already visited Portugal. Articles on international news websites from the period of 2013 to 2018 from eight quality papers of the four main tourism markets of Portugal (UK, Spain, France, and Germany) and the awards attributed to destination Portugal were gathered and analysed. A literature review of publications about tourism was also performed. The results of this study highlight that international tourists consider Portugal a welcoming country that naturally benets from exceptional landscapes, climate, gastronomy and wines, enjoyable tourism experiences, as well as a rich cultural heritage, historical cities, villages, customs and traditions, and a unique Portuguese lifestyle. These international tourists are also willing to recommend Portugal as a tourist destination